Dalits in Different Eyes and Their Identity Crisis - Neupane, Devi Kumari (AMC Journal, 2024)
I have portrayed Dalits from diverse theoretical and philosophical standpoints. The main objective of this article is to explore the Dalits and their identity crisis from various insights. Documental study/desk review is used. A critical approach to generating information, united with thematic analysis in data interpretation, and the use of both digital and manual libraries, are the core areas of study in this field. These sources yielded the knowledge that Dalits no matter whether they are male or female are rich because of their traditional skills, occupations and distinctive capacities. Despite these strengths, they have been struggling for their identities. Dalit women are triply oppressed as stigmatized Dalit, as Dalit women, and as powerless beings. For generations, Dalits including women have been subjected to various forms of exclusion, denial, dominance, and discrimination. Dalit women's case is even worse as they are at the bottom of the social hierarchy. When viewed from various viewpoints, Dalits continue to be intricate and varied. Questions of representation, empowerment, and belonging continue to influence Dalits' individual and collective identities as they traverse this challenging landscape. People in these communities frequently experience an identity crisis as a result of these perceptions of Dalits, divided between the desire for greater social inclusion and their traditional caste-based identity. Their fight for recognition and justice within a broader context of historical injustices and international power dynamics emphasises their experiences and voices that are often ignored in mainstream discourse.